Do Loan Loss Provisions Affect the Credit Fluctuations in China's Banking System?. Issue 11 (2nd September 2019) - Wang, Zongrun; Xie, Nan; Jin, Yanbo
ABSTRACT: The global financial crisis of 2008 sparked new ideas on pro-cyclical transmission in the financial system. The accounting treatment method of loan loss provisions differs between the accounting standards that banks use and the supervisory rules of banks. This fundamental difference has attracted wide attention from academics and regulators. This article studies whether bank loan loss provisions affect credit fluctuation in China's banking system. We divide loan loss provisions into discretionary and non-discretionary loan loss provisions. We find that non-discretionary loan loss provisions result in greater credit fluctuation, whereas discretionary loan loss provisions have no significant impact on credit fluctuation. Further evidence shows that the relation between non-discretionary loan loss provisions and credit fluctuations does not vary among different types of banks. Overall, our study shows that non-discretionary loan loss provisions can increase credit fluctuation and therefore strengthen banks' pro-cyclical behavior.